MANUSCRIPTS OF LITHUANIAN TATARS: HISTORY AND PERSPECTIVE OF RESEARCH - MIŠKINIENĖ, GALINA (Knygotyra, 2010)
The Lithuanian Tatar manuscript tradition is unique cultural phenomenon which was born in the 16th century and an composed exclusive heritage feature of Grand Duchy of Lithuania. In the mid-16th century, the oldest Tatar manuscripts (Kitab, Chamail, Tejvid, Tefsir) were written in the old Belarusian or Polish languages but in Arabic script. Manuscripts in the Slavic languages contain also texts in the Arabic and Ottoman Turkish languages. Specialists had already paid attention to this manuscript literature in the mid-19th century. However, only in the end of the 20th century comprehensive and purposeful studies were started when Professor Anton Antonovič published his monograph Белорусские тексты , писанные арабским письмом, и их графико-орфографическая система (Vilnius, 1968). When this rich layer of Eastern culture was further researched, the graphic and textual analysis and the analysis of thematic manuscripts were started by Galina Miškinienė, Andrzej Drozd, Czesław Łapicz, Paul Suter.Nevertheless, those studies are insufficient, because most of manuscripts stored in archives (their content, characteristics of graphic, literature, speech, religion and culture) are poorly known even by specialists of this branch. Till now, only few Tatar manuscript sources have
Keywords: ...